On Certain Types of Lower Minimal structure Actions - Fieras Joad Obead Al-ysaary (Al-Qadisiyah Journal of Pure Science, 2018)
The main aim of this work is to create a new types of Lower minimal structure action namely -action, -action and -action. Also, we gave restriction and the relation among the certain types of Lower minimal structure action.